Management of Teachers’ Spiritual Competence In The Perspective of Qur’an: A Study of Surah Taha Verses 9-47 In The Perspective of Muhammad Ali Ash-Shabuni - Slamet, Ariyanto; Imam, Makruf (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
The aim of this study is to evaluate the management of teachers’ spiritual competence in Surah Taha verses 9-47, through planning, organization, implementation, and control, from the prespective of Muhammad Ali Ash-Shabuni. The literature review was conducted using the libarry research method to obtain relevant data. The analysis showed that the planning and organization phase consists of five main parts, namely: 1) in verses 9-13, Allah SWT has chosen us, particulary the teachers, to carry on the message of Prophet Muhammad, just as Musa was selected as a prophet; 2) in verses 14-23, the text emphasizes the importance of worshipping Alalh SWT, believing in the Day of Judgment and accepting death as inevitable, acknowledging that all creations are the mercy of Allah SWT, and trusting only Him; 3) verses 24-36 underline the value of mutual cooperation and assistance when the need arises; 4) in verses 37-40, recall Allah’s blessings and favors, which inspire devotion and worship to Him; 5) subsequently, in verses 41-47, the teacher should prioritize ongoing learning. Verse 9 provides guidance fro implementation, while Surah Qaf verses 16-17 address control